The Salmonella pathogenicity island-2 subverts human NLRP3 and NLRC4 inflammasome responses. Issue 2 (4th October 2018) - Bierschenk, Damien; Monteleone, Mercedes; Moghaddas, Fiona; Baker, Paul J; Masters, Seth L; Boucher, Dave; Schroder, Kate
Abstract: Inflammasomes are signaling hubs that activate inflammatory caspases to drive cytokine maturation and cell lysis. Inflammasome activation by Salmonella Typhimurium infection or Salmonella -derived molecules is extensively studied in murine myeloid cells. Salmonella -induced inflammasome signaling in human innate immune cells, is however, poorly characterized. Here, we show that Salmonella mutation to inactivate the Salmonella pathogenicity island-2 type III secretion system (SPI2 T3SS) potentiates S . Typhimurium-induced inflammasome responses from primary human macrophages, resulting in strong IL-1β production and macrophage death. Inactivation of the SPI1 T3SS diminished human macrophage responses to WT and ΔSPI2 Salmonella . Salmonella ΔSPI2 elicited a mixed inflammasome response from human myeloid cells, in which NLR family CARD-domain containing protein 4 (NLRC4) and NLR family PYRIN-domain containing protein 3 (NLRP3) perform somewhat redundant functions in generating IL-1β and inducing pyroptosis. Our data suggest that Salmonella employs the SPI2 T3SS to subvert SPI1-induced NLRP3 and NLRC4 inflammasome responses in human primary macrophages, in a species-specific immune evasion mechanism. The Gram-negative bacterium Salmonella Typhimurium suppresses human macrophage inflammasome responses via the Salmonella Pathogenicity Island 2.